The art and science of dermal formulation development - Brown, Marc D.; Williams, A. C. (Adrian C.) (Boca Raton, Florida : CRC Press, 2019)
The Art and Science of Dermal Formulation Development is a comprehensive guide to the theory and practice of transdermal and topical formulation development, covering preclinical studies, evaluation, and regulatory approval. It enables the reader to understand the opportunities and challenges in developing products and how risks can be mitigated. Over the last 25 years, expertise in this area has declined whilst drug delivery systems for other administration routes have developed significantly. The advantages offered by transdermal and topical drug delivery remain compelling for sectors including the pharmaceutical industry, personal care, and cosmetics. This text addresses the dearth of expertise and discusses how skin can be a route of delivery and the processes in formulation development, but how such an application is very different to that used for oral, IV, and other administration routes.
3.2.2.11 Amino Acid-Based Enhancers3.2.2.12 Peptides; 3.2.3 Synergy between Chemical Penetration Enhancers; 3.2.4 General Comments on Penetration Enhancers; 3.3 Permeation Retardation; 3.4 Drug and Formulation Manipulation Strategies; 3.4.1 Prodrugs; 3.4.2 Ion-Pairing; 3.4.3 Eutectic Systems/Depression of Permeant Melting Point; 3.4.4 Supersaturation; References; Chapter 4: Physical and Technological Modulation of Topical and Transdermal Drug Delivery; 4.1 Introduction; 4.2 Vesicles; 4.2.1 Liposomes; 4.2.2 Non-Ionic Surfactant Vesicles (Niosomes)
OCLC-licensed vendor bibliographic record.
Keywords: Transdermal medication; Transdermal medication -- Research -- Methodology; Dermatologic agents -- Absorption and adsorption; Skin -- Physiology; MEDICAL / Pharmacology; MEDICAL / Dermatology; MEDICAL / Pharmacy